Seasonal shifts in community composition and proteome expression in a sulphur‐cycling cyanobacterial mat - Sharon L. Grim; Dack G. Stuart; Phoebe Aron; Naomi E. Levin; Lauren Kinsman‐Costello; Jacob R. Waldbauer; Gregory J. Dick (Environmental Microbiology, 2023)
Seasonal changes in light and physicochemical conditions have strong impacts on cyanobacteria, but how they affect community structure, metabolism, and biogeochemistry of cyanobacterial mats remains unclear. Light may be particularly influential for cyanobacterial mats exposed to sulphide by altering the balance of oxygenic photosynthesis and sulphide‐driven anoxygenic photosynthesis. We studied temporal shifts in irradiance, water chemistry, and community structure and function of microbial mats in the Middle Island Sinkhole (MIS), where anoxic and sulphate‐rich groundwater provides habitat for cyanobacteria that conduct both oxygenic and anoxygenic photosynthesis. Seasonal changes in light and groundwater chemistry were accompanied by shifts in bacterial community composition, with a succession of dominant cyanobacteria from Phormidium to Planktothrix , and an increase in diatoms, sulphur‐oxidizing bacteria, and sulphate‐reducing bacteria from summer to autumn. Differential abundance of cyanobacterial light‐harvesting proteins likely reflects a physiological response of cyanobacteria to light level. Beggiatoa sulphur oxidation proteins were more abundant in autumn. Correlated abundances of taxa through time suggest interactions between sulphur oxidizers and sulphate reducers, sulphate reducers and heterotrophs, and cyanobacteria and heterotrophs. These results support the conclusion that seasonal change, including light availability, has a strong influence on community composition and biogeochemical cycling of sulphur and O 2 in cyanobacterial mats.